Discursive Strategies in the Reform of the Public Security Law in the Province of Córdoba, Argentina - Caccia, Ana Clara (2026)
This article aims to analyze the discursive strategies deployed during the parliamentary debate on the Reform of the Public Security Law in Córdoba, Argentina. In particular, it examines the speeches delivered during that legislative session and explores the conditions of possibility that enabled such strategies. The methodological approach of this study is grounded in the perspective of discourse field analysis. To this end, a corpus was constructed consisting of the stenographic records of the Legislature of Córdoba and official documents from the Comprehensive Plan for Citizen Security and Crime Prevention. Additionally, a qualitative strategy was employed, based on in-depth semi-structured interviews with current and former members of the Community Police, as well as with officials from the Provincial Government. Three core areas of controversy were identified, around which both the parliamentary debate and this public policy were structured: the role assigned to the police force, the concept of security, and the involvement of citizens in security-related matters.